Kapasitas Masyarakat dan Identifikasi Potensi Wisata Untuk Pengembangan Pariwisata Kota Lubuklinggau - Okma Yendri (Jurnal Abdimas Pariwisata, 2022)
Community Capacity and Identification of Tourism Potential for Lubuklinggau City Tourism Development This Community Service activity aims to increase the capacity of the people of Lubuklinggau City in the tourism sector and identify the existing tourism potential. In this activity, there are three approaches taken, including Participatory Rural Appraisal (PRA), Community-based development, and participatory. Collecting data using Focus Group Discussion (FGD) techniques and field observations. The tourism potentials identified in this community service activity include Magic Hill, Temam Waterfall and Watervang Dam, while cultural potentials include women's Batik Durian weaving activities and the art of twilight. It can be concluded that in the development of Lubukinggau City as a tourist city, assistance activities are still needed such as promotion and e-commerce training, scouting and English training, and improvement of the mitigation system in the Magic hill area to improve the concept.